Cognitive profile in idiopathic autonomic failure: relation with white matter hyperintensities and neurofilament levels. Issue 6 (18th May 2022) - Cani, Ilaria; Sambati, Luisa; Bartiromo, Fiorina; Asioli, Gian Maria; Baiardi, Simone; Belotti, Laura M. B.; Giannini, Giulia; Guaraldi, Pietro; Quadalti, Corinne; Romano, Luciano; Lodi, Raffaele; Parchi, Piero; et al.
Abstract: Objective: To disclose the nature of cognitive deficits in a cohort of patients with idiopathic autonomic failure (IAF) by exploring the relation among cognitive functions, cardiovascular autonomic failure (AF) and clinical progression to another α‐synucleinopathy (phenoconversion). Methods: We retrospectively identified all patients with a clinical diagnosis of IAF who underwent a comprehensive neuropsychological evaluation, clinical examination and cardiovascular autonomic tests from the IAF‐BO cohort. Brain magnetic resonance imaging (MRI) studies and cerebrospinal fluid (CSF) analysis, including neurofilament light chain (NfL), Alzheimer disease core biomarkers, and α‐synuclein seeding activity were further evaluated when available. Correlations among cognitive functions, clinical features, cardiovascular AF, cerebral white matter hyperintensities (WMH) load, and CSF biomarkers were estimated using Spearman correlation coefficient. Results: Thirteen out of 30 (43%) patients with IAF displayed cognitive deficits (CI) mainly concerning executive functioning. Seven out of 30 (23%) met the criteria for mild cognitive impairment (MCI). The diagnosis of CI and MCI was not associated with phenoconversion or autonomic function parameters, including duration and severity of neurogenic orthostatic hypotension, presence and severity of supine hypertension, and nocturnal dipper profile. Twenty patients underwent a brain MRI and CSF analysis. MCI was related to WMH load ( r = 0.549) and NfL levels ( r = 0.656), while autonomic function parameters were not associated with either WMH or NfL levels. Interpretation: Cardiovascular AF and phenoconversion, underlying the spreading of neurodegeneration to the central nervous system, were not independent drivers of cognitive dysfunction in IAF. We identified WMH load and NfL levels as potential biomarkers of the neural network disruption associated with cognitive impairment in patients with IAF.